2018
DOI: 10.1039/c7ta09118d
|View full text |Cite
|
Sign up to set email alerts
|

Synergic coating and doping effects of Ti-modified integrated layered–spinel Li1.2Mn0.75Ni0.25O2+δ as a high capacity and long lifetime cathode material for Li-ion batteries

Abstract: The Ti-modified Li1.2Mn0.75Ni0.25O2+δ with core–shell structure has showed better cycling stability than the pristine one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…A peak of a Mn 3 + /4 + redox couple of around 4.0 V is also commonly seen in a disordered LMNO structure. [20,21] In addition, there was no significant difference in the CV responses between the samples of a conventional structure and a 3D structure, which was reasonable, since that structure did not affect the chemical properties. The results from CV measurement were consistent with the voltage profiles, as shown in Figure 2g.…”
Section: Ultra-thin Coating and Three-dimensional Electrode Structurementioning
confidence: 53%
See 3 more Smart Citations
“…A peak of a Mn 3 + /4 + redox couple of around 4.0 V is also commonly seen in a disordered LMNO structure. [20,21] In addition, there was no significant difference in the CV responses between the samples of a conventional structure and a 3D structure, which was reasonable, since that structure did not affect the chemical properties. The results from CV measurement were consistent with the voltage profiles, as shown in Figure 2g.…”
Section: Ultra-thin Coating and Three-dimensional Electrode Structurementioning
confidence: 53%
“…As shown in Figure f, the coated samples (green line range) showed a 40 % smaller difference between the anodic and cathodic peaks than those of the uncoated samples (yellow line range), which suggested a smaller polarization and better conductivity of the coated samples. It was also observed that the coated samples had more significant N i2+/4+ peaks at 4.5 to 4.8 V and Mn 3+/4+ at 3.6 to 4.3 V than the uncoated samples did, which indicated increased amounts of Ni 2+/4+ and Mn 3+/4+ redox couples . The peak of the Ni 2+/4+ redox couple is known as one peak for an ordered LMNO structure, while the Ni exhibits two‐step reactions, including Ni 3+/4+ and Ni 2+/3+ for a disordered LMNO structure.…”
Section: Figurementioning
confidence: 93%
See 2 more Smart Citations
“…Among various doping elements such as Ru, [6] Cr, [7] V, [8] etc., Ti has a lot of advantages including abundant, non-toxic, high bonding with oxygen which can stabilize framework. [9,10] For example, Zhao et al substituted Ti for Mn in 0.5Li2MnO3-0.5LiNi1/2Mn1/2O2, resulting in improving the performance of the cathode material by suppressing transition metal ions dissolution during cycling. [11] Thackeray et al also reported that Ti substituted Mn and Ni in Li(Mn0.46Ni0.46Ti0.05Li0.02)O2 improve capacity as well as cycling stability compared with undoped sample.…”
Section: Introductionmentioning
confidence: 99%